1984
DOI: 10.1111/j.1432-1033.1984.tb08160.x
|View full text |Cite
|
Sign up to set email alerts
|

The primary structure of teichuronic acid in Bacillus subtilis AHU 1031

Abstract: Structural studies were carried out on the acidic polysaccharide fraction obtained from lysozyme digest of the cell walls of Bacillus subtilis AHU 1031. The polysaccharide fraction contained N-acetylmannosaminuronic acid (ManNAcA), N-acetylglucosamine (GlcNAc), glucose, glycerol and phosphorus in a molar ratio of 2 :2 :4:1 :I, together with glycopeptide components. The results of analyses involving Smith degradation, chromium trioxide oxidation, methylation and proton magnetic resonance spectroscopy led to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Recent studies on cell walls of some Bacillus strains have revealed the structure of their acidic polymer components, including poly(glycerol phosphate) (15), poly(hexosylglycerol phosphate) (14), poly(ribitol phosphate) (17), poly(N-acetylglucosamine phosphate) (18), and mannosaminuronic acidcontaining teichuronic acid (28,29) as well as the structure of the junctions of these polymers to peptidoglycan. To examine whether there are any structural similarities between LTAs and WTAs in the respective Bacillus strains, we investigated the structure of LTAs isolated from these Bacillus strains.…”
mentioning
confidence: 99%
“…Recent studies on cell walls of some Bacillus strains have revealed the structure of their acidic polymer components, including poly(glycerol phosphate) (15), poly(hexosylglycerol phosphate) (14), poly(ribitol phosphate) (17), poly(N-acetylglucosamine phosphate) (18), and mannosaminuronic acidcontaining teichuronic acid (28,29) as well as the structure of the junctions of these polymers to peptidoglycan. To examine whether there are any structural similarities between LTAs and WTAs in the respective Bacillus strains, we investigated the structure of LTAs isolated from these Bacillus strains.…”
mentioning
confidence: 99%
“…The repeating unit (Fig. 6) contains glucose, N-acetylmannosaminuronic acid, and N-acetylglucosamine with glucose branches, about half of which carry glycerol phosphate units, joined to the N-acetylglucosamine units (Yoneyama et al, 1984). The polymer consists of some 12-15 repeating units, terminating at the reducing end in an N-acetylglucosaminyl residue that is probably linked through a sugar-I-phosphate linkage to muramic acid phosphate.…”
Section: Teichuronic Acidsmentioning
confidence: 99%
“…In B. licheniformis the linkage does not involve a specialized unit of the type found with teichoic acids but instead consists of a sugar-I-phosphate linkage between the reducing terminal N-acetylgalactosamine and the primary hydroxyl group of an Nacetylmuramic acid residue in the peptidoglycan (Wyke and Ward, 1977b;. The teichuronic acid in walls of B. subtilis AHU 1031 consists of some 12-15 repeating units terminating in an N-acetylglucosamine residue that is probably linked through a sugar-I-phosphate linkage to muramic acid (Yoneyama et al, 1984). …”
Section: Teichuronic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several questions remain unanswerable: (i) which of ␤-galactofuranose and ␣-galactopyranose is present at the reducing end of PS-2, (ii) which residue of peptidoglycan is responsible for the linkage between PS-2 and peptidoglycan, and (iii) whether a di-or trisaccharide linkage unit is included as found in some other bacteria (11,16,29). We attempted to isolate both PS-1-peptidoglycan and PS-2-peptidoglycan complexes by lytic enzyme digestion using lysozyme and N-acetylmurami- on May 10, 2018 by guest http://jb.asm.org/ dase SG to obtain information about the linkage region; however, the purified cell walls were resistant to such enzymatic digestions.…”
mentioning
confidence: 99%